PENGARUH STRUKTUR MODAL DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN - Haryono, Selly Anggraeni; Fitriany, Fitriany; Fatima, Eliza (Jurnal Akuntansi dan Keuangan Indonesia, 2017)
The objective of this study is to empirically examine non-linear (quadratic) effect of capital structure on firm performance (Tobin’s q dan ROA) and also the effect of Multiple Large Shareholder Structure (MLSS) and institutional ownership on firm performance. The sample is a non-financial company listed on the Indonesia Stock Exchange with the study period 2009-2012. Data obtained from Data Stream and IDX website. Using fixed effect panel regression, this research finds that the capital structure has a quadratic (concave) effect on firm performance measured by ROE with maximum point at debt to equity of 1.95. This result indicates that the total debt that maximizes the company's performance is 1.95 of the total capital. The study also finds that increasingly large multiple shareholder structures (MLSS) will decrease firm performance, while higher institutional ownership will improve company performance.